Highly selective chromoionophores for ratiometric Na+ sensing based on an oligoethyleneglycol bridged bithiophene detection unit. Issue 18 (16th April 2019) - Moser, Maximilian; Thorley, Karl J.; Moruzzi, Floriana; Ponder, James F.; Maria, Iuliana P.; Giovannitti, Alexander; Inal, Sahika; McCulloch, Iain
Abstract : A series of nine novel Na + selective ratiometric optical probes (S1–S9 ) have been developed and evaluated both by computational and experimental means. Abstract : Rapid and efficient measurement of sodium ion concentrations will benefit future studies and healthcare due to the importance of sodium to many biological processes. Ratiometric optical probes, where light absorption wavelengths shift according to ion concentration, can be used as a quick measurement method. In contrast to the currently available UV absorbing probes, we have synthesised a series of sensors which absorb in different regions of the visible spectrum. In addition to measurement by conventional UV-Vis spectroscopy, this also enables analysis of sodium ion concentration from colorimetry, opening the door to faster and cheaper analysis. Finally, the optical properties of the dyes were well reproduced by computational methods, with and without the presence of sodium, enabling acceleration of design of future materials.